CHANGES FUNCTION AND ROLE IN REGULATING CHILD NINIK MAMAK NEPHEW DI KANAGORIAN KOTO TELUK BERINGIN KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Olipio, Romansyah; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted at Kanagorian Koto Teluk Beringin Bay Gunung Toar Kuantan Singingi disrtrict. This study aims to find out what are the functions and roles change ninik mamak dikanagorian koto teluk beringin Bay, and to look at the factors that influence changes in the function and role in regulating child ninik mamak nephew. In analyzing this research, quantitative descriptive, ie data that has been processed then be made in the form of a table, and then presented in the form of words that describe the specific circumstances and is easy to understand about the function and role of ninik mamak and changes.The results of this study show a change in the function and role ninik mamak of the at Kanagorian Koto Teluk Beringin Bay is in regulating childrens nephew, in the case of disputes, inheritance, education, and in the field of marriage functions and roles ninik mamak not undergo a change. This caused by several factors, namely technological factors: the development of increasingly sophisticated technology today makes the function and role of ninik mamak changes to childrens nephew, the influence of other culture: entry and the development of another culture amid public life today make the function and role of ninik mamak more reduced, politics and economics: understanding is not in line with the political and economic nephew children ninik mamak less able to make the function and role changes, and educational factors: low education ninik mamak making function and its role is less appreciated by his nephew children.Keywords: Functions, Roles and Changes